Infak Ramadan programme_ #BPACare contributions bring joys to school children - UMP, PNC (2019)
In an effort to make the holy month of Ramadan more exceptional, Universiti Malaysia Pahang (UMP)’s Marketing and Student Admission Division (BPPP) feted 44 orphans and children of less privileged families from SK Serandu, Pekan during the Infak Ramadan and khatam of the al-Quran programmes that were held on May 24, 2019.